Robustness of the rule‐learning effect in 7‐month‐old infants: A close, multicenter replication of Marcus et al. (1999). Issue 1 (24th February 2022) - Geambașu, Andreea; Spit, Sybren; van Renswoude, Daan; Blom, Elma; Fikkert, Paula J.P.M.; Hunnius, Sabine; Junge, Caroline C.M.M.; Verhagen, Josje; Visser, Ingmar; Wijnen, Frank; Levelt, Clara C.
Abstract: We conducted a close replication of the seminal work by Marcus and colleagues from 1999, which showed that after a brief auditory exposure phase, 7‐month‐old infants were able to learn and generalize a rule to novel syllables not previously present in the exposure phase. This work became the foundation for the theoretical framework by which we assume that infants are able to learn abstract representations and generalize linguistic rules. While some extensions on the original work have shown evidence of rule learning, the outcomes are mixed, and an exact replication of Marcus et al.'s study has thus far not been reported. A recent meta‐analysis by Rabagliati and colleagues brings to light that the rule‐learning effect depends on stimulus type (e.g., meaningfulness, speech vs. nonspeech) and is not as robust as often assumed. In light of the theoretical importance of the issue at stake, it is appropriate and necessary to assess the replicability and robustness of Marcus et al.'s findings. Here we have undertaken a replication across four labs with a large sample of 7‐month‐old infants ( N  = 96), using the same exposure patterns (ABA and ABB), methodology (Headturn Preference Paradigm), and original stimuli. As in the original study, we tested the hypothesis that infants are able to learn abstract "algebraic" rules and apply them to novel input. Our results did not replicate the original findings: infants showed no difference in looking time between test patterns consistent or inconsistent with the familiarization pattern they were exposed to. Abstract :